Batak Toba Women's Struggle to Protect Traditional Frankincense Forests in a Geographical Perspective - Ratih Baiduri; Elly Prihasti Wuriyani; Muharrina Harahap; Ayu Febryani (JURNAL GEOGRAFI, 2025)
Batak Toba oral literature represents women as farmers and discoverers of frankincense trees, highlighting the connection between women and nature. The ecofeminism perspective views this relationship as a form of resistance against environmental exploitation and gender injustice. The purpose of this article is to focus on the struggle of the Batak Toba Sipituhuta-Pandumaan ethnic women in preserving the indigenous frankincense forest against Toba Pulp Lestari (TPL). The research method that will be used is qualitative research with a descriptive approach. Phase I (first) will be observing, identifying, and classifying the types of Batak Toba literary works that contain Batak Toba cultural values related to environmental conservation efforts. In the second stage, participatory observations and in-depth interviews were conducted with selected informants, followed by analysis, discussion, and conclusions. The struggle of women in protecting the frankincense forest has long been represented in folklore, portraying women as the discoverers of the tree that saved their family's economy. Within the forest-owning community, women also play a role in protecting men from potential violence during conflicts. Supported by KSPPM, the prolonged struggle of Sipituhuta-Pandumaan women resulted in the recognition of their customary forest by the government in 2021. Their close connection to the frankincense forest stems from their feminine nature, characterized by a deep concern for environmental preservation and household sustainability, which is perceived as a cultural burden.